Epstein–Barr Virus+ Smooth Muscle Tumors as Manifestation of Primary Immunodeficiency Disorders - Magg, Thomas; Schober, Tilmann; Walz, Christoph; Ley-Zaporozhan, Julia; Facchetti, Fabio; Klein, Christoph; Hauck, Fabian (Frontiers in Immunology, 2018)
Epstein–Barr virus positive (EBV+) smooth muscle tumors (SMTs) constitute a very rare oncological entity. They usually develop in the context of secondary immunodeficiency caused by human immunodeficiency virus infection or immunosuppressive treatment after solid organ transplantation. However, in a small fraction of predominantly pediatric patients, EBV+ SMTs may occur in patients with primary immunodeficiency disorders (PIDs), such as GATA2 and CARMIL2 deficiency. In secondary immunodeficiencies and when the underlying condition can not be cured, the treatment of EBV+ SMTs is based on surgery in combination with antiretroviral and reduced or altered immunosuppressive pharmacotherapy, respectively. Importantly, without definitive reconstitution of cellular immunity, long-term survival is poor. This is particularly relevant for patients with EBV+ SMTs on the basis of PIDs. Recently, allogeneic hematopoietic stem cell transplantation resulted in cure of immunodeficiency and EBV+ SMTs in a GATA2-deficient patient. We propose that in the absence of secondary immunodeficiency disorders patients presenting with EBV+ SMTs should be thoroughly evaluated for PIDs. Allogeneic hematopoietic stem cell transplantation should be taken into consideration, ideally in the setting of a prospective clinical trial.